Fault Interpretation Based on Similarity and Curvature Attributes in F3 Netherlands: Interpretasi Sesar Berdasarkan Atribut Similarity dan Curvature di Lapangan F3 Netherlands - Nadea Arie Saragih; Faizar Farid; Juventa Juventa (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2022)
F3 Southern North Sea Netherlands Basin field is an oil and gas field that has a complex fault structure and stratigraphy due to compressional tectonic movements during the Late Cretaceous and Tertiary eras. Information on the presence of faults can act as a trap or migration which then greatly affects oil and gas production and the injection process. A seismic attribute analysis of similarity and curvature was used to interpret the presence of fault structures to obtain information on the presence of subsurface faults in the F3 Netherlands field. The interpretation of the similarity attribute calculation results shows that the faults are marked with a minimum similarity value of 0.77, 0.68, and 0.66 at the time slices Z = 400ms, 1700ms, and 1800ms. The maximum value of most post-positive curvature represents the presence of an ascending fault block and the maximum value of the most negative curvature represents the presence of a descending fault block at the same time incision. Based on the similarity and curvature attribute calculations, it can be interpreted that the major faults in Top Zechstein to Upper Pliocene and the presence of successive faults on Top Zechstein to Base Lower Cretaceous are faults due to the formation of the Zechstein salt dome intrusion